Analysis of the Impact of Artificial Intelligence Technology on the Development of Students’ Academic Writing Skills in the Digital Learning Era - Nur Hidayat; Wildan Muafan; Elma Nurjannah; Akhmad Affandi; Rosidah (Academic Bright Collaboration, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed academic practices, particularly in supporting the development of students’ academic writing. However, empirical evidence explaining how AI utilization, automatic feedback, and personalized learning contribute to writing performance in higher education remains limited. This study examines the effects of AI utilization, AI-based automatic feedback, and AI-driven personalized learning on Students’ Academic Writing Skills (SAWS). Using an explanatory quantitative approach with a cross-sectional design, data were collected from 88 Indonesian university students through purposive sampling. Partial Least Squares–Structural Equation Modeling (PLS-SEM) was employed to evaluate the measurement and structural models. The findings show that Automatic Feedback Based on AI (AFBAI) is the strongest predictor of SAWS (β = 0.531; p = 0.000). The Utilization of AI Technology (UAIT) also has a significant positive effect (β = 0.290; p = 0.007), indicating that frequent use of AI tools contributes to improved writing skills. Conversely, Personalized Learning Based on AI (PLBAI) has no significant direct effect (β = 0.053; p = 0.350). The structural model demonstrates substantial predictive power with an R² value of 0.660. AI technologies play an essential role in enhancing academic writing performance, especially through automated feedback and consistent utilization. However, AI-driven personalized learning systems still require further optimization and deeper user engagement to meaningfully support the development of complex writing competencies.